Factors influencing staff complying with SOP: a study at Road Transport Department (RTD) Kota Bharu, Kelantan / Amyzulliana Zulkifli and S. Sarifah Radiah Shariff - Zulkifli, Amyzulliana; Radiah Shariff, S. Sarifah (Universiti Teknologi MARA Press (Penerbit UiTM), 2023)
Standard Operating Procedure (SOP) is an effective tool for controlling everyday transactions in Road Transport Department (RTD). There are in the form of a written document that elaborates every small activity of the RTD transaction from its conception to completion. The SOP helps to create a proper "communication chain" among people working in RTD, which are customers, runners, and RTD personnel. The SOP gives clarity on when and who should implement the activities, SOP is easily formulated and adjusted to the needs of the development of applicable policy. SOP gives an abstract of different activities to be taken in a specific transaction. The step-by-step actions enlisted by SOP are of great assistance in keeping a check on actions taken or transactions to be conducted. Thus, SOP works as a guiding path. Though the use of SOP is inevitable, there is resistance to adopt the stringent principles and practices of SOP. The objectives of this paper are to determine the factors contributing to the non-compliance of the standard operating procedure (SOP) and to study the suitability of instruments used in order to analyse the factors presented in the Literature Review in the context of RTD Branches in Kelantan. Data were collected using an online questionnaire and analysed using Descriptive Analysis, Correlation coefficient, Cronbach´s Alpha, and Multiple Regression Analysis.